Self-ignition of natural fuels: Can wildfires of carbon-rich soil start by self-heating?. (July 2017) - Restuccia, Francesco; Huang, Xinyan; Rein, Guillermo
Abstract: Carbon-rich soils, like histosols or gelisols, cover more than 3% of the Earth's land surface, and store roughly three times more carbon than the Earth's forests. Carbon-rich soils are reactive porous materials, prone to smouldering combustion if the inert and moisture contents are low enough. An example of soil combustion happens in peatlands, where smouldering wildfires are common in both boreal and tropical regions. This work focuses on understanding soil ignition by self-heating, which is due to spontaneous exothermic reactions in the presence of oxygen under certain thermal conditions. We investigate the effect of soil inorganic content by creating under controlled conditions soil samples with inorganic content (IC) ranging from 3% to 86% of dry weight: we use sand as a surrogate of inorganic matter and peat as a surrogate of organic matter. This range is very wide and covers all IC values of known carbon-rich soils on Earth. The experimental results show that self-heating ignition in different soil types is possible, even with the 86% inorganic content, but the tendency to ignite decreases quickly with increasing IC. We report a clear increase in ambient temperature required for ignition as the IC increases. Combining results from 39 thermostatically-controlled oven experiments, totalling 401 h of heating time, with the Frank-Kamenetskii theory of ignition, the lumped chemical kinetic and thermal parameters are determined. We then use these parameters to upscale the laboratory experiments to soil layers of different thicknesses for a range of ambient temperatures ranging from 0 °C to 40 °C. The analysis predicts the critical soil layer thicknesses in nature for self-ignition at various possible environmental temperatures. For example, at 40 °C a soil layer of 3% inorganic content can be ignited through self-heating if it is thicker than 8.8 m, but at 86% IC the layer has to be 1.8 km thick, which is impossible to find in nature. We estimate that the critical IC for a ambient temperature of 40 °C and soil thickness of 50 m is 68%. Because those are extreme values of temperature and thickness, no self-heating ignition of soil can be expected above the 68% threshold of inorganic content. This is the first in-depth experimental quantification of soil self-heating and shows that indeed it is possible that wildfires are initiated by self-heating in some soil types and conditions.